Cellular and molecular mechanisms of asbestos carcinogenicity: implications for biopersistence. - Barrett, J C (1994)
Carcinogenic agents can influence the carcinogenic process either by mutating critical target genes or by increasing the number of cells at risk for mutations. Cytogenetic and molecular studies of asbestos-related cancers indicate that inactivation or loss of multiple tumor suppressor genes occurs during lung cancer development. Aneuploidy and other chromosomal changes induced by asbestos fibers may be involved in genetic alterations in asbestos-related cancers. Furthermore, asbestos fibers may influence the carcinogenic process by inducing cell proliferation, free radicals, or other promotional mechanisms. Therefore, asbestos fibers may act at multiple stages of the carcinogenic process by both genetic and epigenetic mechanisms. Biopersistence is undoubtedly important in fiber carcinogenicity. However, the time required for a fiber to remain in the lung to exert a cancer-related effect is difficult to specify.